Techno-economic and environmental assessment of electrification scenarios in waterborne public transport - Cedrillo Ledesma, Andrea Celeste; Jutblad, Nils (My University, 2023)
The shipping industry currently stands for around 3% of the world’s greenhouse gas emissions (GHGs), and is predicted to increase its emissions significantly until 2050 unless mitigation efforts are made. For shorter routes and smaller vessels, electrifi cation has been identified as a promising method of decarbonisation. In this study, a techno-economic and environmental assessment framework was used in order to analyze the cost and environmental effects of electrifying public transport ferries op erating on the Göta Älv river in Gothenburg. Four different electrification scenarios were constructed based on information obtained from literature and interviews with relevant stakeholders. For these scenarios, the results suggest that three out of four would have lower costs than the baseline. The lowest cost of ownership was observed when optimizing the on-board battery capacity by deposition charging several times during the day, leading to around 8% lower costs than the baseline. As for the environ mental calculations, the results indicate a possible decrease in GHGs of about 77-90% of greenhouse gas emissions in the electrification scenarios compared to the baseline, with zero emissions of NOx , SO2 and particulate matter (PM) on a local level compared to present case. The scenarios showing the largest mitigation potential utilized wire less opportunity charging which allows for a significant decrease in on-board battery capacity compared to the baseline, thereby reducing upstream emissions from battery production. Overall, the study shows that there are positive environmental and cost ef fects of fully electrifying the Göta Älv ferries, which could act as inspiration for decision makers within waterborne public transport.
Keywords: Waterborne public transport; Electrification; Electric ferries; Case Study